Propaganda material. Funeral of Karl Marx in London, Highgate. Left: Liebknecht; fourth from the right: Engels - He Kongde,
Propaganda material. Funeral of Karl Marx in London, Highgate. Left: Liebknecht; fourth from the right: Engels.